The phoenix project a novel about IT, DevOps, and helping your business win - Kim, Gene; Behr, Kevin; Spafford, George (Portland, OR IT Revolution, 2018)
Bill has 90 days to fix a behind-schedule IT project, or his entire department will be outsourced. Fortunately, he has the help of a prospective board member, whose "Three Ways" philosophy might just save the day.
"5th anniversary limited edition"--Cover.
"Updated and expanded edition."
Management theory presented in novel form.
Includes bibliographical references (pages 424-431).
Keywords: Information technology -- Management -- Fiction; Information technology -- Planning -- Fiction; Information technology -- Security measures -- Fiction; Knowledge management -- Fiction; Information technology -- Management; Information technology -- Planning; Information technology -- Security measures; Knowledge management